An investigation of the potential role of students in decision making in the management and administration of secondary schools : a case study - Chinsamy, Dhanasagren (Rhodes University, Faculty of Education, Department of Education, 1995)
As South Africa prepares to reconstruct its education system for a post-apartheid, democratic society, many facets of educational life will of necessity come under re-examination. One such area is that of school governance which traditionally was the domain of principals, teachers and more recently parents, with little, if any, input by students. After 1985, however, with the formation of the Congress of South African Students (CaSAS), backed by the National Education Co-ordinating Committee (NECC), the demand for student participation in the management of schools began to gain momentum. Parent-Teacher -Student Associations (PTSA's), although not recognised by the education authorities, were established in many black schools throughout the country. They afforded students the opportunity to become involved, as equal partners with teachers and parents, in decision-making in the management of secondary schools. During the past decade, however, the question of student participation in decision-making in the management of schools has become a point of controversy. The aim of this study was to investigate the potential role of students in decision-making in the administration and management of secondary schools. For this purpose case studies were conducted in two schools with active student participation in joint decision-making. The schools were selected after a preliminary investigation of the state of PTSA's in schools in the greater Durban area. Questionnaires and semi-structured interviews with teacher, parent and student representatives and principals and non-participant observation of PTSA meetings, workshops and social functions were used to survey attitudes and opinions pertinent to this study. The results of the study indicate that student participation in the management of schools is crucial for the creation of a climate of learning and teaching and that it is seen in itself as an integral part of the process of students' development. The study also points to the dilemma that students face in participating jointly with parents and teachers in decision-making while maintaining their autonomy. The recommendations that emerge from the study include the involvement of students as equal partners in decision-making in secondary schools, the establishment of Internal Disciplinary Committees in which students participate, the appointment of a member of staff as a liaison officer for student affairs with the task of establishing a Students' Representative Council (SRC) and the implementation of training programmes that would assist students in joint decision-making. The study acknowledges the existence of conflict between the participants but proposes that such conflict can be constructively addressed tbrough "creative consensus" that would benefit both the participants and the school. The researcher recommends that for the present, students should not be involved in any discussions of teacher misconduct and that students should not be entrusted with handling the finances of the school without teacher or parent supervision. However, in keeping with the developmental approach adopted in the study, it is envisaged that when the element of trust is developed between students and teachers, students would be allowed to participate in these sensitive areas of decision-making.
Keywords: Student participation in administration -- South Africa; Student-administrator relationships -- South Africa